Towards Integration of Energy Storage Systems for Carbon Neutral Buildings : A Review of Multi-Criteria Decision Making Approaches - Lü, Xiaoshu; Lu, Tao; Tervola, Pekka (Atlantis Press, 2023)
Building sector consumes about 40% of the global energy consumption and emits over 30% of the global energy-related CO2 emissions. It is one of the most resource-intensive sectors and the main contributor of the environmental emissions. Additionally, the amount of greenhouse gas emissions is increasing remarkably due to the rapid growth in urbanization. Distributed energy resources (DERs) offer opportunities to support the deployment of large shares of renewable energy sources (RES) in order to meet the sustainability goals of reducing carbon emissions and increasing building resilience. DERs consist primarily of energy generation and energy storage systems (ESS) which are located near to the end-users of buildings, allowing easily integration of RES and realization of carbon neutrality. However, widespread adoption of renewable energy is challenging because of its intermittent nature. Energy supply does not satisfy with the demand, back-up supply from ESS is therefore required to solve the problems. ESS are of great importance for balancing supply and demand mismatches and offering the opportunity to replace fossil fuels with large shares of renewable penetration on DERs to eventually achieve zero-carbon emissions in buildings. Due to numerous factors that influence ESS, selection of the suitable energy storage technologies for specific building applications presents a challenge. In the literature, different criteria have been suggested to contrast ESS’ strengths and weaknesses for different applications. Methodologically, multi-criteria decision making (MCDM) has been widely employed in planning ESS. This paper aims to provide a critical review of MCDM for the deployment solutions of RES and ESS in carbon neutral building applications. A conceptual illustration is also presented to synthesize the literature review and explain the key methodologies of MCDM.
Keywords: Energy storage; buildings; multi-criteria decision making; review; fi=Energiatekniikka|en=Energy Technology|